ANALISIS DAMPAK PENGGUNAAN SISTEM INFORMASI AKADEMIK (SIAKAD) TERHADAP EFEKTIVITAS ADMINISTRASI KAMPUS DI STKIP HARAPAN BIMA - Hardyanti, Hardyanti; Fauzi, Azra (Jurnal Ilmiah Administrasita', 2024)
The Academic Information System (Siakad) has been implemented at STKIP Harapan Bima to enhance campus administrative effectiveness. This study aims to analyze the impact of Siakad on four main indicators: time efficiency, service quality, data accessibility, and user satisfaction. A quantitative approach with a survey design was employed, involving 50 respondents consisting of students, lecturers, and administrative staff. The results indicate that Siakad positively impacts all indicators, with high average scores across the board. Time efficiency and data accessibility were the most appreciated aspects by users, while the primary challenges identified were unstable internet connectivity and system errors. To improve the effectiveness of Siakad, enhancements to network infrastructure, regular system updates, and technical training for new users are recommended. This study provides crucial recommendations for further development of Siakad as a more efficient and effective campus administration tool.